F(x) = 2x + 1
To find the inverse of a function you just need to switch the x by y or vice-versa:
-> y = 2x + 1
-> x = 2y + 1
After that you isolate the y again:
-> 2y = x - 1
-> y = (x-1)/2
-> f^-1 (x) = (x-1)/2
Answer:
Answer:
The value of f(0) is Option (A) : - 2
Greatest error is half smallest measuring unit. It's measured to 0.1 cm , half that is 0.05 cm answer D.
7x (2x^2 - 3) is your answer my dude/lady
F-1:
y=x+9
y-9=x
x-9=f-1
f-1(14)=14-9=5 f-1(5)=5-9=-4 f-1(-5)=-5-9=-14 f-1(25)=25-9=16
f(14)=14+9=24 f(5)=5+9=14 f(-5)=9-5=4 f(25)=25+9=34